(untitled) (The Pakistan Development Review, 2016)
It is to access that the microcredit has a positive impact on education and healthcare spending of the borrowed households is controversial in developing countries literature or not. This study reports evidence, from Pakistan for this debate, while utilising data from PPHS- 2010 (Pakistan Panel Household Survey). Propensity score matching (PSM) has been used to investigate the impact of household credit on healthcare and education spending by the poor. In addition to matching statistically identical borrowers with non-borrowers, the method controls for household pre-treatment assets and income. These may be correlated with unobservable factors affecting credit participation as well as outcomes of interest. The estimates from binary as well as multiple ordered treatment effect show insignificant impact of borrowing on education and significant and positive impact on healthcare spending. JEL Classification: D13, C14 Keyword: Matching; Household Credit; Per-capita Income; Education and Healthcare Spending